Residual contaminants in milk - Nevijo Zdolec; Mirza Hadžiosmanović; Lidija Kozačinski; Željka Cvrtila; Ivana Filipović (Mljekarstvo)
Various chemical agents are used during the whole production chain of milk and dairy products. Production of feedingstuffs is accompanied with pesticide usage, which may remain in environment, thus are transported through feeding into animals, animal products and finally in human organism. Preparation procedure and storage conditions of feed also influence on milk safety in the sense of mycotoxins entering into the food chain. Chemical agents are, on daily basis, used on dairy farms either as detergents or disinfections. The residuals of cleaning agents might remain in milk if the cleaning agents and its dosage are not performed adequately. Besides already mentioned agents, a great influence in milk production can bee seen through veterinary drugs usage, particularly antibacterial drugs (mastitis). Proper application of drugs and by following legal recommendation, a by-reactions can be avoided such as allergic reaction in humans, development of resisting bacteria or even undesirable influence on starter cultures in dairy products manufacture. The maximum residue limits, monitoring plan as well as sampling procedures are set up within the harmonization of Croatian and European legislation, in order to provide official control of residues in foodstuffs of animal origin.